Pengaruh Project Based Learning Terhadap Kemampuan Berpikir Peserta Didik: Studi Meta Analisis - Darwas, Rahmadini; Sepriana, Rina; Yulastri, Asmar; Irfan, Dedy; Jalinus, Nizwardi (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to conduct a meta-analysis of research findings regarding the impact of Project-Based Learning (PjBL) on students' thinking skills.Method – This study employs a meta-analytic approach, where data is collected from previous studies that examine the impact of PjBL on students' cognitive thinking skills, use diverse samples in terms of educational contexts and levels, and Integrate findings from previous research to obtain a quantitative perspective on the effect of PjBL. The study employs a meta-analysis method using the random effect Restricted Maximum Likelihood model. A total of 25 articles from the Scopus and Google Scholar databases were analyzed. Publication bias was tested using funnel plot, Egger's test, and Fail-safe N test to ensure data reliability.Findings – The results of the meta-analysis showed that the effect size analyzed comprehensively in all articles obtained a value of 0.223, with a confidence interval value determined at 95%, the estimated upper value of the effect size obtained was 0.377 and the lower limit value was 0.069. The results of the study revealed a significant difference in the mean effect size at the school level between junior high schools, high schools, and higher education. The data used in this study were also free from bias as stated in the results of the funnel plot statistical test, Egger's test, and the Fail-safe N test. Based on these findings which were analyzed holistically, it can be concluded that PjBL can improve students' thinking skills in the learning process. Research Implications – These findings provide empirical evidence that PjBL can be used as an effective teaching strategy to enhance students' thinking skills. This study supports the development of structured project-based educational practices to achieve more optimal cognitive outcomes.